Physical playing pattern and ecological validity of the YoYo-IR1 Test in U-19 female basketball - Nabli, M. A.; Chamari, K. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: Understanding the physical activity, the physiological profile and the repeated sprint bouts (RS) nature of U-19 female basketball during official games could help coaches to plan their training. However, they are not extensively researched, as well as, the ecological validity of the Yo-Yo Intermittent-Recovery Test level-1 (YoYo-IRT1). The aims of this study were to determine: 1) the physical and physiological demands of U-19 elite-female basketball; 2) the relationship between the YoYo-IRT1 and game physical-activity; 3) and the RS nature in U-19 basketball. METHODS: Computerized motion-analysis, heart-rate (HR) and blood lactate concentration [La] were measured in 30 players during eight U-19 games (the play-off stage of Tunisian league). They performed YoYo-IRT1. A RS was defined as a minimum of 3-sprints, with recovery of less than 21-sec in-between any of sprints` set. RESULTS: Players spent ~13%, ~29.2% and ~25.2% of total live-time in high, moderate to low-intensity activities, whereas in-between efforts` recovery corresponded to ~32.6%. They spent ~57% of playing-time in high HR-zone (85-95%HRmax). Players performed an average of 6.4 RS per-player per-game, each bout including 3 to 5-sprints. The mean of sprint duration was 2.1±0.4 sec, with a mean recovery time equal to ~8.8-sec. A significant correlation was also observed between [La] and the time spent in high-intensity activity for the 5-min of play prior to blood sampling (r=0.52, P<0.05). A significant correlation was found between YoYo-IRT1 performance and the %time spent in sprint and total high-intensity activities (r=0.67, P=0.001 and r=-0.72, P<0.001, respectively). CONCLUSIONS: This study showed that U-19 elite-female basketball is a moderate to high-intensity activity, with the Yo-Yo-IR1 test being a good-predictor of physical game-performance.